MySQL database service revealed : running MySQL as a service in the Oracle Cloud Infrastructure - Bell, Charles A. (Charles Andrew), 1962- (Apress, 2023)
Access all the information you need to begin using the MySQL Database Service (MDS) in the Oracle Cloud Infrastructure (OCI). MDS is Oracle’s new platform as a service (PAAS) offering for open-source database users. This book covers getting started with an account in OCI, gives a brief overview of OCI services available, and provides a short tutorial on MDS. Reading this book helps you take advantage of the powerful OCI features by building your own MySQL database in the cloud. Examples in this book center around running MDS in OCI, and include several of the popular use cases as well as advice on how to implement them. In addition, you will learn more about the related MDS OCI features, such as the high availability features currently available. Finally, you will learn how to back up and restore your data as well as how to get your data into and out of the cloud. The skills you learn in this book will help you get started using MDS and letting Oracle do the heavy lifting of managing MDS operations and implementation.